Services Policies in Transition Economies : On the EU and WTO as Commitment Mechanisms - Eschenbach, Felix; Hoekman, Bernard (World Bank, Washington, DC, 2012)
The authors analyze the extent to which the EU-15 and 16 transition economies used the WTO General Agreement on Trade in Services (GATS) to commit to service sector policy reforms. They compare GATS commitments with the evolution of actual policy stances over time. While there is substantial variance across transition economies on both actual policies and GATS commitments, the authors find an inverse relationship between the depth of GATS commitments and the "quality" of actual services policies as assessed by the private sector. In part this can be explained by the fact that the prospect of EU accession makes GATS less relevant as a commitment device for a subset of transition economies. But for many of the non-EU accession candidates, the WTO seems to be a weak commitment device. One explanation is that the small size of the markets concerned generates weak external enforcement incentives. The authors' findings suggest greater collective investment by WTO members in monitoring and the need for transparency to increase the benefits of WTO membership to small countries.